Crude Palm Oil Moisture Reduction: Design and Implementation of an Arduino UNO-Based Automated Heating Control System - Syem Vicra Lumban Gaol; Andi Prayogi; Raden Aris Sugianto (Academic Bright Collaboration, 2026)
Purpose – Crude Palm Oil (CPO) quality is strongly influenced by moisture content because excessive water can accelerate hydrolysis, increase free fatty acid formation, promote oxidation, and reduce storage stability. This study aimed to develop and functionally evaluate a low-cost Arduino-based automated heating control prototype to support laboratory-scale CPO moisture-reduction experiments. Methods – This study employed a Research and Development method with a quantitative experimental orientation. The prototype integrated Arduino UNO as the main controller, DHT22 for ambient humidity monitoring, MAX6675 with a Type-K thermocouple for direct CPO temperature measurement, I2C 16×2 LCD for data display, a two-channel 5V relay for heater switching, a 350 W water heater, and LED-buzzer indicators. Functional testing was conducted through observation of sensor readability, LCD display, relay switching, heater response, and integrated system operation. Findings – The results showed that all main components operated according to their intended functions. The system could read humidity and CPO temperature, display real-time data, activate and deactivate the heater through relay control, and provide visual and audible indicators. Research Implications – The prototype provides a functional baseline for automated CPO heating control. However, it does not directly measure actual CPO moisture content because DHT22 only reads ambient humidity. Originality – This study offers a low-cost Arduino-based prototype for supporting CPO heating-control experimentation.